Evaluating managerial competence of small, medium and micro-entrepreneurs to ensure sustainable economic development in eThekwini municipal area - Sijuwade Adedayo Ogunsola; Nobubele Potwana; Felix Chikosha (Economics, Management and Sustainability)
This research investigates the influence of Small, Medium, and Micro Entrepreneurs (SMMEs) on sustainable economic development in the eThekwini Municipal Area of South Africa. It focuses on the capability of SMME managers and operators to efficiently and effectively utilise available resources, ensuring their enterprises make a meaningful contribution to sustainable economic growth. Data was gathered from a diverse set of SMMEs in the eThekwini Municipal Area using a simple random sampling method, with 229 entrepreneurs participating. Key findings reveal that entrepreneurs underscore the importance of knowledge, skills, value judgments, behavioural traits, and social networks in establishing and operating successful businesses. A notable challenge identified was their limited ability to identify viable business opportunities. Nevertheless, these entrepreneurs demonstrate a commitment to maintaining their local environments and providing employment opportunities to community members, and some contribute to community development initiatives. The primary recommendation emerging from this study is providing support and tools to assist potential entrepreneurs in effectively recognising and seizing business opportunities.